Implicatures Generated from Non-Observances Maxim in The Interview of The Indonesian President: conversational implicature in Joko Widodo's interview - Tiara Adena; Zuindra Zuindra; Hendra Mulia (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
The aims of this research are to find out the conversational implicatures generated by President Jokowi during an interview with BBC News Indonesia. Additionally, it aims to identify which cooperative principles are disregarded to produce these implicatures. The research data consists of dialogues from the interview. To analyze the data, the researcher applies the theory of implicature and the non-observance maxims by Grice. In data analysis, the researcher employs the qualitative data method by Miles and Huberman (2014). The research findings reveal that there are 16 specific implicatures identified out of 18 data instances in the conversation, while the other 2 are general implicatures. Furthermore, the researcher identifies various forms of non-observance maxims, with the most frequently found was the flouting of the maxim of quantity.